Neighborhood social capital and infant physical abuse: a population-based study in Japan - Fujiwara, Takeo (Int J Ment Health Syst, 2016)
PURPOSE: We sought to investigate the relationship between neighborhood social capital and infant physical abuse using a population-based sample of women with 4-month-old infants in Japan. METHODS: A questionnaire was administered to women who participated in a 4-month health checkup program (n = 1277; valid response rate, 80 %). We inquired about their perceptions of the level of trust in their neighborhood (an indicator of “social capital”) as well as the availability of support from their personal social networks. Infant physical abuse during the past month was assessed by self-reports of spanking, shaking or smothering. RESULTS: The prevalence of infant physical abuse at 4 months of age was 9.0 % (95 % confidence interval [CI], 7.6–10.7 %). Women living in trusting neighborhoods were less likely to report infant physical abuse compared to those living in areas with low neighborhood trust (odds ratio [OR] 0.25, 95 % CI 0.06–0.97). In addition, women with supportive social networks were less likely to report infant physical abuse (OR 0.59, 95 % CI 0.36–0.99). CONCLUSIONS: In addition to one’s personal social network, social trust in the neighborhood was independently associated with lowered risk of infant physical abuse. To prevent infant abuse, interventions should consider strengthening community social bonds in addition to strengthening the social network of isolated mothers.